2x^2
Chat with our AI personalities
No. 2 to the third power = 2 x 2 x 2 = 8 3 to the second power = 3 x 3 = 9
Just X to the second power minus nine. You can't subtract nine from x to the second power unless you know what x is.
f(x) = (x^2)(e^x)f'(x) = e^x((x^2)+2x) - i thinkf"(x) = ?--------f(x) = (x^2)(e^x)apply the power rulef'(x) = (x^2)(e^x) + (2x)(e^x)apply the power rule to the first part and apply the power rule to the second part, then add those togetherf''(x) = [(x^2)(e^x) + (2x)(e^x)] + [(2x)(e^x) + (2)(e^x)]simplifyf''(x) = (e^x)(x^2 + 4x +2)I got it right. It checked out on my calculator.
Would you mind typing it out for me? I don't quite understand exactly what you are asking. For example, x to the second power minus 4x over x to the second power minus 16 would be... x^2-4x/x^2-16 Do you mind typing it out like that? Because what you wrote makes no sense at all.
3x^2 - 27 = = 3(x^2 - 9) = 3(x^2 - 3^2) = 3(x - 3)(x + 3)